2001
DOI: 10.1023/a:1010373113060
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Women with inadequate prenatal care were recruited to a multi-component parenting intervention study. Because it was anticipated that this high-risk population might present challenges to retention, a variety of strategies were employed to maintain their participation in the study. This report reviews the results of these retention efforts and compares the population that completed the study versus those that terminated prior to study completion. Two hundred and eighty-six women were randomized to an intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 9 publications
2
43
1
Order By: Relevance
“…For example, in a study examining parent interventions in a sample of low-income mothers, Katz and colleagues noted an attrition rate of 41% by 12 months. 30 This indicates that, although retention is a continuing issue for long-term preventive interventions, the results of the current study are likely valid. Finally, measures of responsive parenting and physical punishment were obtained through parent-report, which may be subject to social desirability bias, given the controversial nature of parental discipline.…”
Section: Discussionmentioning
confidence: 75%
“…For example, in a study examining parent interventions in a sample of low-income mothers, Katz and colleagues noted an attrition rate of 41% by 12 months. 30 This indicates that, although retention is a continuing issue for long-term preventive interventions, the results of the current study are likely valid. Finally, measures of responsive parenting and physical punishment were obtained through parent-report, which may be subject to social desirability bias, given the controversial nature of parental discipline.…”
Section: Discussionmentioning
confidence: 75%
“…Home visitation programs designed to enhance parenting can only prove beneficial if families are engaged and actively participating in program interventions (Katz et al, 2001; Peterson, Luze, Eshbaugh, Jeon, & Kantz, 2007; Spieker, Solchany, McKenna, DeKlyen, & Barnard, 2000). In a study of families enrolled in an Early Head Start Program that offered comprehensive child development and family support services to low-income families, researchers found that approximately one third of the mothers were extremely difficult to engage or did not engage in program interventions or activities (Spieker et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that enhanced parenting can mitigate or buffer the adverse effects of poverty on early childhood development (Duncan & Brooks-Gunn, 2000; Olds et al, 2004). Katz et al (2001) had an attrition rate of 41% in a multicomponent parenting intervention even though multiple retention strategies were included. They found that those families that dropped out early from the program were less likely to provide developmentally appropriate home environments for their child.…”
Section: Introductionmentioning
confidence: 99%
“…These retention strategies are commonly used in other studies. [4][5][6][7] We found the use of an SMS text out service 1 month before a scheduled home visit was useful in identifying changes to participants' details, identifying disconnected mobile phone numbers and allowing alternative methods of contacting participants. With the increasing use of mobile phones in the community, many participants no longer used a landline, and we found them more likely to communicate via text message.…”
mentioning
confidence: 99%
“…These retention rates were similar to other studies. [4][5][6][7] A review of the circumstances under which participants dropped out of the trial was conducted and is shown in Table 1. Participants who dropped out of the program tended to be younger mothers on a lower income with a lower level of education.…”
mentioning
confidence: 99%